The Influence of Career Development and Competence on Performance Mediated by Organizational Commitment on Employees of the Maluku Province Education Quality Assurance Center - La Idrus; Novalien Carolina Lewaherilla; F. Leuhery; Gerrit M Pentury (Sean Institute, 2026)
This study aims to analyze the influence of career development and competency on employee performance with organizational commitment as a mediating variable among employees of the Maluku Province Education Quality Assurance Center. The research method used is a quantitative approach with data collection techniques through distributing questionnaires to all employees. Data analysis was conducted using the path analysis method to test the direct and indirect relationships between variables. The results of the study indicate that career development, competency, and organizational commitment have a positive and significant effect on employee performance. Career development does not affect organizational commitment. Organizational commitment is not able to mediate the effect of career development on performance. In addition, organizational commitment is proven to be able to mediate the relationship between competency and performance. This indicates that the better the career development and competency possessed by employees, the more their commitment to the organization will increase, which ultimately has an impact on improved performance. The implication of this study is the importance of organizations in improving employee career and competency development programs to strengthen organizational commitment and improve performance optimally.